A kinetic study on the conversion of nylon 12 to methyl 12-hydroxydodecanoate in supercritical MeOH in the presence of carboxylic acid. (December 2017) - Kamimura, Akio; Ikeda, Kosuke; Suzuki, Shuzo; Kato, Kazunari; Matsumoto, Hiroshi; Kaiso, Kouji; Yoshimoto, Makoto
Abstract: Polyamides were effectively converted into hydroxyl esters by treatment with supercritical MeOH in the presence of glycolic acid. This transformation progressed smoothly over a period of 240 min, and the presence of glycolic acid accelerated the reaction. Kinetic analyses of the depolymerization of nylon 12 were performed by measuring the product distribution in the reaction mixture. The chemoselectivity of hydroxyl ester formation was linearly dependent on the amount of glycolic acid used. The product distribution of the reaction using pivalic acid was also measured. Simulations based on the actual time-course data enabled the estimation of kinetic parameters. The obtained kinetic parameters revealed that the rate constant for the formation of the hydroxyl ester was significantly enhanced by the presence of glycolic acid. These results clearly indicate that the monomeric unit, an amino ester, underwent a bimolecular substitution reaction with glycolic acid. Based on these results, we proposed a reaction mechanism for the formation of hydroxyl esters. Arrhenius plots of the reaction rates were used to effectively estimate the activation energy for each step.